Education mathematics in real life and visualization in periodical in Lithuania between the two word wars - Ragalytė, Birutė; Paukštienė, Alma (Lietuvos matematikos rinkinys, 2013)
Teaching mathematics real life and vizualization in periodical between the two word wars are introduced in article This paper analyzes the interwar Lithuanian periodicals emphasis in mathematics teaching in real life. Much attention in the interwar Lithuania pedagogical periodical offered for pupils to develop independence. This article discusses what proposals teaching mathematics in real life and visualization present A. Nemickas, S. Vainberg, A. King, B. Ketarauskas, V. Augustauskas, K. Budrys et al.